Increasing mental toughness through COVID-19 gymnastics in adult people - Komarudin; Sandey Tantra Paramitha; Muhammad Gilang Ramadhan; Geraldi Novian (UIR Press, 2022)
The danger of this virus has forced the government to implement various regulations to reduce the level of spread and infection, one of which is by staying at home. Staying at home and staying away from socialization that is usually done makes individuals get various mental problems which of course have an impact on the human condition itself, so it is important for individuals to still have mental toughness. In this study, the authors wanted to examine the effect of implementing COVID-19 gymnastics that had been made previously on mental toughness in adults people in Indonesia. The experimental method with a one-group pretest-posttest design was used in this study. COVID-19 gymnastics for 6 weeks was given to 150 subjects by professional gymnastics instructors. Before and after being given treatment, the subject filled out the Mental Toughness Inventory (MTI) which was prepared beforehand to obtain data, after which data analysis was carried out using SPSS Version 24. The results showed that there was a significant effect of COVID-19 gymnastics on increasing mental toughness in adults people in Indonesia. In addition, the COVID-19 gymnastics was proven to be effective in providing an increase in results between the pretest and the posttest by 3.6%. This study concludes that the application of COVID-19 gymnastics has a positive effect on mental toughness in adults people in Indonesia, so it can be an alternative activity to avoid various mental health problems, especially during a pandemic like this. The author suggests that every individual remains active in exercising even in situations and conditions that are full of limitations, one of which can be done by doing COVID-19 gymnastics.